Health expenditures, environmental quality, and economic development: State-of-the-art review and findings in the context of COP26 - Xing, Zhenjiang; Liu, Xia (Frontiers in Public Health, 2022)
During the recent decades, world is facing the issue of human health affected by numerous factors. Among others, environmental; governance and economic growth are regarded as more critical in this regard. The current study aims to explore the impacts of greenhouse gas (GHG) emissions, governance indicators and gross domestic product (GDP) on human health expenditures captured by domestic health expenditures and capital health expenditure. In doing so, regulatory quality (RQ), rule of law (RL), GDP, greenhouse gas emissions and human capital (HC) are utilized as key factors. This study investigates the period from 1996 to 2020, for the case of China; one of the largest pollution emitting economies across the globe. Using the time series specifications, this study found that the variables are cointegrated. The empirical results of fully modified ordinary least square, dynamic ordinary least square, and canonical cointegration regression suggest that economic development and regulatory quality are adversely affecting human health expenditure. However, greenhouse gas emissions; regulatory quality, and human capital significantly improve human health by increasing health expenditure in China. Based on the empirical results, policies are suggested regarding human health improvement, improved governance quality, and environmental sustainability. The study discusses the empirical conclusions and implications as per COP 26 declarations.